MEKANISME PEROLEHAN ILMU DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Maria Ulfah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
Knowledge is one of the truth sources on humankind. It is believed that knowledge is a main factor that shapes human’s culture, history, and civilization. Knowledge construction is a compound that has particular differences. The mechanism of acquiring knowledge according to the philosophy of Islamic education consists of several types: first, mechanism of acquiring knowledge through experience; second, mechanism of acquiring knowledge through rationale and; third, mechanism of acquiring knowledge through revelation. These mechanisms create some important implications in Islamic education philosophy, particularly on learning theories.